Saliva use as a lubricant for anal sex is a risk factor for rectal gonorrhoea among men who have sex with men, a new public health message: a cross-sectional survey. (3rd March 2016) - Chow, Eric P F; Cornelisse, Vincent J; Read, Tim R H; Lee, David; Walker, Sandra; Hocking, Jane S; Chen, Marcus Y; Bradshaw, Catriona S; Fairley, Christopher K
Abstract : Background: Apart from penile–anal intercourse, other anal sexual practices (rimming, fingering and saliva use as a lubricant for anal sex) are common among men who have sex with men (MSM). The aim of this study is to evaluate whether these anal sexual practices are risk factors for rectal gonorrhoea in MSM. Method: A cross-sectional survey was conducted among MSM attending Melbourne Sexual Health Centre between 31 July 2014 and 30 June 2015. Rectal gonorrhoea cases were identified by culture. Results: Among 1312 MSM, 4.3% (n=56) had rectal gonorrhoea. Other anal sexual practices were common among MSM: receptive rimming (70.5%), receptive fingering or penis dipping (84.3%) and using partner's saliva as a lubricant for anal sex (68.5%). Saliva as a lubricant (adjusted OR 2.17; 95% CI 1.00 to 4.71) was significantly associated with rectal gonorrhoea after adjusting for potential confounding factors. Receptive rimming and fingering or penis dipping were not statistically associated with rectal gonorrhoea. The crude population-attributable fraction of rectal gonorrhoea associated with use of partner's saliva as a lubricant for anal sex was 48.9% (7.9% to 71.7%). Conclusions: Saliva use as a lubricant for anal sex is a common sexual practice in MSM, and it may play an important role in gonorrhoea transmission. Almost half of rectal gonorrhoea cases may be eliminated if MSM stopped using partner's saliva for anal sex.